A51 Children's trip to school and psychological well-being. Issue 2 (June 2015) - Waygood, Edward; Friman, Margareta; Olsson, Lars; Taniguichi, Ayako
Abstract: Background: Since 2000, considerable research has focused on explaining children's travel such as mode choice, with particular focus on physically active modes as a contribution to children's physical well-being. However, much less research has looked at other domains of children's well-being such as psychological. This research examines several questions relating children's travel to their psychological well-being. Methods: Questionnaires were developed that included psychological measures to children's travel diaries. Relevant to this paper psychological questions included: a general satisfaction with their trip to school; trip-specific stressful-relaxing scale; trip-specific bored-alert scale; and trip-specific appreciation (worst-best imaginable) scale. The questionnaires were completed by children aged 10-12 in Canada, Sweden, and Japan. The timing of the distribution aimed at limiting climate differences so that surveys were first completed in Canada (October-early November), then Sweden (November-December), and finally in Japan (January). Relevant statistical analysis (ANOVA) is used to compare results by mode (active travel, car, public transport) and gender. Only the trip to school is included in this study. Results: Current results are limited to Canada, though for the conference comparisons across countries are expected. H1 (satisfaction with trip to school is dependent on gender and mode): gender, not statistically significant (NSS); mode, statistically significant. AT>car>PT. H2 (the level of stressful-relaxing is related to gender and mode): gender, SS; mode, NSS. Boys>girls. H3 (the level of bored-alert is related to gender and mode): both are NSS. H4 (the level of appreciation is related to gender and mode): gender, SS; mode, NSS. Boys>girls. Conclusions: Children who travelled to school by active modes are more likely to be very satisfied with their trip to school. Boys are more relaxed during their trip and they are more likely to feel that their trip to school is close to being the best imaginable. Future work should examine what is associated with trips that are higher ranked by these measures.